Disappearance of Residual Nevi and Graying of Eyelashes after Skin Grafting for a Divided Nevus: A Case Report - Megumi Nishiyama; Mikiko Shimomura; Narumi Taguchi; Ami Kuwabara; Risako Ito; Akinari Yoshizawa; Kenichi Kumazawa; Kyoko Baba; Akira Takeda (Journal of Plastic and Reconstructive Surgery, 2025)
We report a case of a 1-year 7-month-old boy who had resection of a divided nevus and skin grafting that resulted in the disappearance of residual nevi, graying of eyelashes, and depigmentation at the donor site of the skin graft and around the lips. The nevus partially remained on the lid margins, although resected as much as possible from the upper and lower eyelids. Nevus cell nevus was the histopathological diagnosis of the resected lesion. Approximately 3 years after surgery, the pigmentation of the nevus remaining on the lid margins started to regress, and the eyelashes at the same sites became gray. Vitiligo gradually developed on the skin grafted from the clavicular region. Approximately 5 years after surgery, the findings remain similar. In this patient, immune responses against nevus cells were established, followed by Sutton's phenomenon accompanied by the destruction of epidermal melanocytes.